(untitled) (Research, Society and Development, 2022)
Periodontal disease is a multifactorial chronic inflammatory process that leads to the destruction of periodontium structures and later tooth loss, impairing oral and general health. Amniotic membrane (AM) attracts attention as a biomaterial for regenerative medicine; its unique architecture ensures excellent biological and mechanical properties. The objective is to analyze the potential of AM in the regeneration of periodontal tissues in induced periodontitis in rats. The sample involved 26 male Rattus norvegicus, Albinos, Wistar rats, weighing approximately 200 to 250g, which after the acclimatization period were randomly divided into groups: Normal group (n=6): the animals were not submitted to any procedure , following the normal course of the experiment; Ligation group (n=10): the animals were submitted to ligation for induction of periodontitis, and after 2 weeks it was removed and continued without treatment; Ligation + AM group (n=10): the animals were submitted to ligation to induce periodontitis, after 2 weeks the ligature was removed and the AM placed around the bone defect. After 4 weeks of AM action, the animals were euthanized and macroscopic, morphometric, histological, histomorphometric and statistical analyzes were performed to evaluate periodontal repair. There was a significant installation of periodontal disease, and after the placement of AM, there was a decrease in alveolar bone loss and probing depth, gain in the level of conjunctival attachment, and periodontal tissues with an aspect of normality. It is concluded that AM stimulates periodontal repair after removing the etiologic agent that was causing periodontitis.